ANALISIS KONDISI BISNIS BPRS DALAM MENGANGKAT PASAR INDUSTRI JASA PERBANKAN - Rahmat Efendi; Mikhriani Mikhriani (UIN Sunan Kalijaga, 2015)
Today many bank grow in area districtof Sleman. Increasingly fiercecompetition makes bank are required to further innovate, and have effectivestrategies in order to achieve customer satisfaction as users of banking service.BPRS MCI is one of the banking institutions located in Sleman, in operationcontinues to show positive developments it is not independent of marketattractiveness and business strength BPRS MCI.The results of this studyhave implemented BPRS MCI right strategy in accordance with the multifactorapproach general electric. This is evidenced by the growing number ofcustomers and impressive profits in each years, product quality and servicequalityare increasing.Key Words : Market attractive and business strategy, marketbanking industry owned by BPRS MCI.